Predicting the Outcome of Voriconazole Individualized Medication Using Integrated Pharmacokinetic/Pharmacodynamic Model - Yang, Ping; Liu, Wei; Zheng, Jiajia; Zhang, Yuanyuan; Yang, Li; He, Na; Zhai, Suodi (Frontiers in Pharmacology, 2021)
Therapeutic drug monitoring is considered to be an effective tool for the individualized use of voriconazole. However, drug concentration measurement alone doesn't take into account the susceptibility of the infecting microorganisms to the drug. Linking pharmacodynamic data with the pharmacokinetic profile of individuals is expected to be an effective method to predict the probability of a certain therapeutic outcome. The objective of this study was to individualize voriconazole regimens by integrating individual pharmacokinetic parameters and pathogen susceptibility data through Monte Carlo simulations (MCSs). The individual pharmacokinetic parameters of 35 hospitalized patients who received voriconazole were calculated based on a validated population pharmacokinetic (PPK) model. The area under the concentration-time curve for free drug / minimal inhibitory concentration (fAUCss / MIC) > 25 was selected as the pharmacokinetic/pharmacodynamic (PK/PD) parameter for efficacy. The cumulative fraction of response (CFR) of the target value were assessed. To verify this conclusion, a logistic regression analysis was used to explore the relationship between actual clinical efficiency and the CFR value. According to the dualistic logistic regression analysis, the minimal inhibitory concentration(MIC) value of different kinds of fungi had a great influence on the effectiveness of clinical treatment. It also showed that the actual clinical efficacy and the CFR value of fAUCss/MIC had a high degree of consistency. The results showed that it is feasible to use individual pharmacokinetic parameters with the pharmacodynamic data to predict clinical outcomes and to formulate individualized drug strategies.